2015
DOI: 10.1093/mnras/stv1120
|View full text |Cite
|
Sign up to set email alerts
|

Mass of intermediate black hole in the source M82 X-1 restricted by models of twin high-frequency quasi-periodic oscillations

Abstract: We apply the relativistic precession model with its variants and the resonance epicyclic model with its variants, based on the frequencies of the geodesic epicyclic motion in the field of a Kerr black hole, to put limits on the mass of the black hole in the ultraluminous X-ray source M82 X-1 demonstrating twin high-frequency quasiperiodic oscillations (HF QPOs) with the frequency ratio near 3:2. The mass limits implied by the geodesic HF QPO models are compared to those obtained due to the model of string loop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 71 publications
0
13
1
Order By: Relevance
“…Our mass estimates are considerably lower than those from thin-disk modeling (Feng & Kaaret 2010) or QPO analysis (Pasham et al 2014). A subsequent analysis of the QPOs by Stuchlík & Kološ (2015) found that the black hole mass estimate from these are strongly model dependent, and given this put a range on the mass as 140 <M BH < 660 M , where the lower masses correspond to a non-spinning black hole, and as such are at odds with our result. In our estimation, we have assumed a face-on inclination of the disk.…”
Section: Comparison With Previous Resultscontrasting
confidence: 73%
“…Our mass estimates are considerably lower than those from thin-disk modeling (Feng & Kaaret 2010) or QPO analysis (Pasham et al 2014). A subsequent analysis of the QPOs by Stuchlík & Kološ (2015) found that the black hole mass estimate from these are strongly model dependent, and given this put a range on the mass as 140 <M BH < 660 M , where the lower masses correspond to a non-spinning black hole, and as such are at odds with our result. In our estimation, we have assumed a face-on inclination of the disk.…”
Section: Comparison With Previous Resultscontrasting
confidence: 73%
“…These models were applied to match the twin HF QPOs and the LF QPO for the microquasar GRO J1655-40 in [47]. Of course, the models can be applied also for intermediate massive black holes [44].…”
Section: A General Properties Of Qpos and Constraints Of Black Hole mentioning
confidence: 99%
“…These models were applied to match the twin HF QPOs and the LF QPO for the microquasar GRO J1655-40 in [45]. Of course, the models can be applied also for intermediate massive BHs [43].…”
Section: General Properties Of Qpos and Constraints Of Black Hole Parmentioning
confidence: 99%